2020
DOI: 10.3390/cancers12092554
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Suppresses Cancer Stem Cells through AMPK Activation and Inhibition of Protein Prenylation of the Mevalonate Pathway in Colorectal Cancer

Abstract: Metformin is a well-known AMPK (AMP-activated protein kinase) activator that suppresses cancer stem cells (CSCs) in some cancers. However, the mechanisms of the CSC-suppressing effects of metformin are not yet well understood. In this study, we investigated the CSC-suppressive effect of metformin via the mevalonate (MVA) pathway in colorectal cancer (CRC). Two colorectal cancer cell lines, HT29 and DLD-1 cells, were treated with metformin, mevalonate, or a combination of the two. We measured CSC populations by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
1
38
0
1
Order By: Relevance
“…Others were mainly about anti-tumor effect, such as inhibition of prostate cancer, colorectal cancer, hepatocellular carcinoma and endometrial cancer, etc [35][36][37][38][39][40][41][42]. In our study, we also found that combination of simvastatin and metformin had a wide range of anti-cancer effects in breast cancer, hepatocellular carcinoma, lung cancer and cervical cancer.…”
Section: Discussionsupporting
confidence: 63%
“…Others were mainly about anti-tumor effect, such as inhibition of prostate cancer, colorectal cancer, hepatocellular carcinoma and endometrial cancer, etc [35][36][37][38][39][40][41][42]. In our study, we also found that combination of simvastatin and metformin had a wide range of anti-cancer effects in breast cancer, hepatocellular carcinoma, lung cancer and cervical cancer.…”
Section: Discussionsupporting
confidence: 63%
“…As an orally ingested drug, its highest concentration is found in the gastrointestinal (GI) tract, and GI derived tumours would most likely be affected 28 , which further indicates that achieved drug concentration play a major role in tumour responses. This is recapitulated in its various mode of action ranging from influence on microbiota 29 , immune modulation 30 , and direct intracellular effect 31 .…”
mentioning
confidence: 99%
“…Activated AMPK promotes tumour cell survival by increasing mitochondrial fatty acid oxidation, mitophagy-mitochondrial fission and mitochondrial biosynthesis [205]. Indeed, CSCs have been reported to be maintained in their stem-like state by AMPK activation although contradictory results on the role of AMPK in CSCs have also been published [217,218]. Nevertheless, in already developed tumours, AMPK appears to act as a tumour promoter, most likely by enhancing the survival of tumour cells under stress conditions [219].…”
Section: Tme Induces a Cancer Stem Cell (Csc) Phenotypementioning
confidence: 99%